Fauna edáfica em sistemas agroflorestais (tradicional e cabruca) e floresta nativa - LIMA, Eduarda Silva de (2021)
The degradation of areas in Brazil is a matter of concern that intensified in 1940 during the occupation of the Amazon. Since then, land use models have been pursued that can minimize damage, such as Agroforestry Systems (SAF). The analysis of edaphic fauna is a means of verifying how these interventions affect environments, given its ecological role. Thus, the objective was to inventory the soil fauna in different seasonality in a Native Forest (FN) and Cabruca (SAFC) and Traditional (SAFT) Agroforestry Systems in Medicilândia-PA through biweekly soil and litter samples. A total of 120 collections (40 per environment) were performed in the litter and soil, divided between rainy season and drought. The faunistic analysis was made by the statistical program R and ANAFAU. 6,440 individuals were raised in 3 phyla, 8 classes and 26 orders. Higher richness occurred in SAFC and greater diversity in NF, but SAFT and NF presented greater similarity. The drought period totaled 2,850 individuals and rainy season 3,590, indicating a strong seasonal influence. The soil gradient obtained higher values among the SAF. Thus, it was noted that the edaphic fauna is an important bioindicator, especially the phylum Arthropoda, and the SAF are excellent for sustainable management.